Pelatihan Pembuatan Nugget Kelor sebagai Alternatif Pemberian Makanan Tambahan (PMT) Anak Balita - Reineldis Elsidianastika Trisnawati; Leliosa Kurnia; Maria F. Kawu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Moringa leaf processing has not been widely carried out in Indonesia. This is due to the lack of public knowledge in utilizing Moringa leaves and the community does not know Moringa leaves as a source of food. Moringa leaves are a natural ingredient with a high nutritional content is also an option to provide additional food for toddlers. This service activity is carried out to increase public knowledge about the importance of nutritious food for children and provide training on making naget from Moringa leaves as an additional food for toddlers. This method of activity is through counseling and training in making Moringa nuggets. This community service provides a change in perspective and increases mothers' knowledge in making supplementary food for toddlers sourced from local food. One of this series of devotions is to train mothers to make breast milk complementary foods and healthy snacks easily and simply but with high nutritional value and hygienic. This service activity has a positive impact on the community, where mothers can do it independently at home about how to make complementary foods and healthy snacks for their children.